Development of Serawai folklore teaching materials based on local wisdom for student literature learning - Indri Pangastuti; Sumiyadi Sumiyadi; Tedi Permadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop teaching materials based on the local folklore of the Serawai ethnic group in Seluma Regency that were feasible, practical, and effective for junior high school literature learning. The main problem addressed was the limited availability of literature teaching materials that integrated local cultural values, which resulted in low contextual relevance for students. The study employed a Research and Development (R&D) method using the Plomp development model, which consisted of preliminary investigation, prototype design, and evaluation stages. Data were collected through observation, interviews, questionnaires, expert validation, and limited field trials conducted in junior high schools. The results indicated that the developed teaching materials based on the Nandai Genai folklore met feasibility criteria in terms of content accuracy, presentation, language use, and graphical design. Teacher and student responses showed highly positive perceptions of the materials’ usability and attractiveness. Furthermore, students’ understanding of literary concepts improved after the implementation of the developed materials. It was concluded that folklore-based teaching materials integrating Serawai local wisdom were appropriate to be used as alternative learning resources and contributed to enriching contextual and meaningful literature learning experiences for students.